Incidence of non-typhoidal Salmonella invasive disease: A systematic review and meta-analysis - Marchello, CS; Fiorino, F; Pettini, E; Crump, JA; Martin, LB; Breghi, G; Canals, R; Gordon, MA; Hanumunthadu, B; Jacobs, J; Kariuki, S; Kim, J-H; et al. (Elsevier, 2021)
Objectives We sought to collate and summarize high-quality data on non-typhoidal Salmonella invasive disease (iNTS) incidence to provide contemporary incidence estimates by location and year. Methods We systematically searched the databases Embase + MEDLINE, Web of Science, and PubMed for articles published on the incidence of iNTS from inception of the database through 8 May 2020 with no language, country, date, or demographic restrictions applied. A meta-analysis was performed to report pooled iNTS incidence as a rate of cases per 100,000 per year. Results Among 13 studies eligible for analysis, there were 68 estimates of incidence. Overall pooled incidence (95% CI) was 44.8 (31.5–60.5) per 100,000 persons per year. When stratified by region, pooled incidence was significantly higher in Africa than Asia, 51.0 (36.3–68.0) compared to 1.0 (0.2–2.5), respectively. Incidence was consistently higher in children aged <5 years compared with older age groups. Incidence displayed considerable heterogeneity in both place and time, varying substantially between locations and over consecutive years in the same location. Conclusions iNTS incidence varies by region, location, age group, and over time. Concerted efforts are needed to address the limited high-quality data available on iNTS disease incidence.